2018
DOI: 10.1186/s12875-018-0765-y
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic test accuracy of rectal examination for prostate cancer diagnosis in symptomatic patients: a systematic review

Abstract: BackgroundProstate cancer is the most common cancer in men in the UK. NICE guidelines on recognition and referral of suspected cancer, recommend performing digital rectal examination (DRE) on patients with urinary symptoms and urgently referring if the prostate feels malignant. However, this is based on the results of one case control study, so it is not known if DRE performed in primary care is an accurate method of detecting prostate cancer.MethodsThe aim of this review is to ascertain the sensitivity, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…In line with this idea, the results obtained herein demonstrate that high urine GOAT levels were associated to a higher risk of developing PCa as well as clinically significant PCa, independently of other parameters clinically relevant for PCa diagnosis and PCa patient's management, including Gleason score, PSA, age and DRE [14,23,24]. Indeed, the diagnostic capacity of urine GOAT levels to identify patients with PCa is comparable to that of the current gold standard plasma PSA levels.…”
Section: Discussionsupporting
confidence: 81%
“…In line with this idea, the results obtained herein demonstrate that high urine GOAT levels were associated to a higher risk of developing PCa as well as clinically significant PCa, independently of other parameters clinically relevant for PCa diagnosis and PCa patient's management, including Gleason score, PSA, age and DRE [14,23,24]. Indeed, the diagnostic capacity of urine GOAT levels to identify patients with PCa is comparable to that of the current gold standard plasma PSA levels.…”
Section: Discussionsupporting
confidence: 81%
“…DRE in the diagnosis of prostate cancer in primary care is also somewhat controversial, but has some stronger evidence for its use. Hamilton et al [ 26 ] found a PPV of 12% (95% CI 5.37) for an abnormal DRE deemed to be malignant by a GP, and a recently published systematic review of all studies of DRE for prostate cancer diagnosis in symptomatic patients in primary care found a pooled PPV of 42.3% [ 5 ]. This data suggests that, despite the reservations of some doctors in performing DREs, primary care clinicians can differentiate between a benign and malignant prostate on examination to a considerable extent.…”
Section: Symptoms and Signsmentioning
confidence: 99%
“…Digital rectal examination (DRE) is recommended in many countries alongside PSA to aid decision-making about referral for diagnostic testing. A recent systematic review suggests that DRE has a high specificity and positive predictive value (PPV) for prostate cancer in symptomatic patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The challenge to orient biopsy decision making is especially present when evaluating patients within the “prostate‐specific antigen (PSA) grey zone” of total PSA (tPSA) 4‐10 ng/mL or 2‐10 ng/mL, a growing cohort of patients with an ageing population, where test performance can vary. The decision to biopsy is further compounded when considering the influence of prostate volume, family history, prior biopsy status and digital rectal exam (DRE) status …”
Section: Introductionmentioning
confidence: 99%
“…The decision to biopsy is further compounded when considering the influence of prostate volume, 4 family history, 5 prior biopsy status 6 and digital rectal exam (DRE) status. 7 The diagnostic tools currently available are generally PSA based, using other forms of PSA, different molecular markers or mathematical combinations of such markers. 8 While they represent an improvement, their performance levels vary depending on the validation cohort used and the intended target population in terms of PSA range, prostate volume and DRE characteristics.…”
Section: Introductionmentioning
confidence: 99%